Efficacy of Plant Growth-Promoting Bacteria Bacillus cereus YN917 for Biocontrol of Rice Blast - Zhou, Hu; Ren, Zuo-hua; Zu, Xue; Yu, Xi-yue; Zhu, Hua-jun; Li, Xiao-juan; Zhong, Jie; Liu, Er-ming (Frontiers in Microbiology, 2021)
Bacillus cereus YN917 obtained from a rice leaf with remarkable antifungal activity against Magnaporthe oryzae, was reported in our previous study. The present study deciphered the possible biocontrol properties. Foliar treatment of rice seedlings by YN917 showed significant disease reduction, the strain was found positive for production of indole-3-acetic acid (IAA), ACC deaminases, siderophores, phosphate solubilizing and major enzymes such as protease, amylase, cellulase and β-1,3-glucanase. Moreover, B. cereus YN917 can also promote seed germination and seedling plant growth. The growth status of rice plants was measured from the aspects of rice plumule, radicle lengths, plant height, stem width, root lengths, fresh weights, dry weights and biomass when YN917 was used as inoculants, thereby indicating that YN917 was a growth-promoting strain. Whole genome sequencing suggests that genes related to the production of IAA, ACC and siderophores were identified in B. cereus YN917, and also has the gene of hydrogen cyanide hcn, Phenazine phz and pyocyanin pcn. In summary, YN917 can not only be used as biocontrol agents to minimize the use of chemical substances in rice blast control, but also can be developed as bio-fertilizers to promote the rice plant growth.